2015
DOI: 10.1186/s12909-015-0473-4
|View full text |Cite
|
Sign up to set email alerts
|

Does a transition in education equate to a transition in practice? Thai stakeholder’s perceptions of the introduction of the Doctor of Pharmacy programme

Abstract: BackgroundPharmacy education and pharmacy practice are facing remarkable changes following new scientific discoveries, evolving patient needs and the requirements of advanced pharmacy competency for practices. Many countries are introducing or undertaking major transformations in pharmacy education. The Thai pharmacy curriculum has been changed from a 5-year BPharm and a 6-year PharmD to only a 6-year PharmD programme. Curriculum change processes usually involve stakeholders, including both internal and extern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 70 publications
3
29
0
Order By: Relevance
“…These advantages included the potential for specialization and better career prospects. This is similar to findings from Chanakit et al, (2015) study, that reported that students in Thailand also thought that the transition to the 6-year program would improve pharmacy competencies from generalists to advance general pharmacists or specialists. In addition, Raman et al (2012) reported that majority of the educated Indians surveyed in their study felt that pharmacists with the Pharm.D.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…These advantages included the potential for specialization and better career prospects. This is similar to findings from Chanakit et al, (2015) study, that reported that students in Thailand also thought that the transition to the 6-year program would improve pharmacy competencies from generalists to advance general pharmacists or specialists. In addition, Raman et al (2012) reported that majority of the educated Indians surveyed in their study felt that pharmacists with the Pharm.D.…”
Section: Discussionsupporting
confidence: 88%
“…This is a definite advantage as Pharm.D. graduates have the skills to approach other health care providers, are more confident and work well within health care teams (Chanakit et al, 2015). Abdelhadi et al (2014) reported in their study that nearly all respondents (90.9 %) reported that Pharm.D.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Thai pharmacy education has transitioned from having two entry-level degrees – a 5-year Bachelor of Pharmacy (BPharm) (with three main tracks: pharmaceutical care [PC], pharmaceutical sciences, and social and administrative pharmacy) and a traditional 6-year Doctor of Pharmacy (PharmD) (PC) program – to a single national 6-year PharmD program (including PC and industrial pharmacy [IP] tracks). 4 , 11 The Pharmacy Council of Thailand mandated that in 2014, marking the 100th year of pharmacy education in Thailand, all Thai entry-level pharmacy curricular will be only a 6-year PharmD program. It is believed that this shift will prepare pharmacy graduates with competencies as a specialist not a generalist to serve the demands of the job market.…”
Section: Introductionmentioning
confidence: 99%